An Investigation of the Influence of Cooperating Teachers in Shaping the Attitudes of Student Teachers Toward the Teaching of English - Peters, William H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
A 24-item questionnaire--Attitudes Toward the Teaching of English--was administered to 34 cooperating teachers and their 34 student teachers from the University of Kentucky. The questionnaire was administered to both groups as a pretest and to student teachers as a posttest. This study investigated the influence of cooperating teachers toward the teaching of English. Results from the pre- and posttests were statistically analyzed. It was found that cooperating teachers did influence the attitudes of student teachers toward the teaching of English. In this study, the influence was in the direction of a more progressive attitude toward the teaching of English. It is recommended that a careful selection of cooperating teachers within teacher education programs be made. (Three tables of statistical data are presented along with a copy of the questionnaire.) (BRB)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cooperating Teachers; English Education; Preservice Teacher Education; Secondary Education; Student Teachers; Teacher Attitudes; Teacher Influence